Konsep Rational Emotive Behaviour Therapy (Rebt) Dalam Usaha Mencegah Juvenile Delinquency - Alvin Koswanto (Sekolah Tinggi Teologi Ekumene Jakarta., 2021)
Social development in adolescents causes them to prefer for a long time with the community or group of peers. This becomes a problem, if teenagers join the wrong community or group, they will have the wrong values so they dare to commit juvenile delinquency. Therefore, this research was written with the aim of providing input to parents and the church in providing rational beliefs or beliefs, so that adolescents do not take actions or actions that violate the norms that exist in society. The method used is library research with the type of textbook analysis. The result of this study is the discovery of the concept of rational belief, to replace irrational adolescent beliefs or beliefs with the hope that adolescents do not show juvenile delinquency.